A method for preparing large-scale powder metallurgy copper-chromium contact material

Through large-scale powder metallurgy technology, copper-chromium contact materials are prepared by mixing, cold isostatic pressure, vacuum sintering, vacuum degassing and hot isostatic pressure, which solves the problems of high investment in large tonnage presses, high mold pressure requirements and low material utilization in the existing technology, and achieves an efficient and low-cost preparation process, and improves the performance of the material.

CN119736509APending Publication Date: 2025-04-01SHAANXI SIRUI ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202510252585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing copper-chrome contact materials have high investment in large tonnage presses, high pressure requirements for molds, high potential risks, low material utilization and high preparation costs.

Method used

Large-scale powder metallurgy technology is used to prepare copper-chromium contact materials through mixing, cold isostatic pressure, vacuum sintering, vacuum degassing and hot isostatic pressure. The specific steps include: mixing chromium powder and copper powder, performing cold isostatic pressure, vacuum sintering, vacuum degassing, and finally obtaining copper-chromium contact material through hot isostatic sintering.

Benefits of technology

The difficulties in the preparation process of large-size contact materials are reduced, the utilization rate of materials is improved, and the preparation cost is reduced. The uniform structure obtained by sub-regional thermal isostatic pressure improves the conductivity, contact resistance, strength and toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736509A_ABST
    Figure CN119736509A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of products made from metal powders, and in particular to a method for preparing a large-size powder metallurgy copper-chromium contact material. The mixed powder contact is prepared by cold isostatic pressing of rods, vacuum sintering and straightening, and reheating isostatic pressing. The method can prepare contact materials with larger specifications, and compared with ordinary molding, the investment in large-tonnage presses and molds is reduced; compared with direct sheathing cold isostatic pressing and reheating isostatic pressing, the rod sintering and straightening process is added, and the straightening process and material loss before the rod sheathing are reduced, thereby greatly improving the material utilization rate and reducing the cost. In addition, the gas content of the material is lower due to the first degassing by cold isostatic pressing, the second degassing by vacuum sintering, and the third degassing by reheating isostatic pressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of products made from metal powders, and in particular to a method for preparing a large-scale powder metallurgy copper-chromium contact material. Background Art

[0002] At present, the common methods for preparing copper-chromium contacts are mixed powder sintering, vacuum casting, and arc melting. Since the mixed powder sintering method uses solid phase sintering, the particle bonding strength is low. During the interruption of the arc chamber, the contact is disconnected from the substrate, and the contact is more easily pulled apart. The contact's anti-welding performance is the best among these processes. The traditional preparation method of mixed powder contacts generally adopts compression molding. This molding method is a single external pressure molding, which has high requirements for the tonnage of the press and the mold. Especially for large-sized contact materials such as direct sizes greater than 70 specifications, a press of 800 tons or more is required for pressing. The cost of a single press is relatively high, and the mold pressure requirements are relatively high. The cost is also relatively increased. The most important potential risks in the pressing process, such as noise and potential dangers caused by mold explosion, are relatively large.

[0003] Patent CN105018768A discloses a high-performance copper-chromium contact material and a preparation method thereof. The method uses copper-chromium mixed powder to directly perform cold isostatic pressing, then vacuum encapsulate, heat, and then perform hot isostatic pressing to prepare the mixed powder contact material. The method processes the copper-chromium alloy rods, which need to go through a processing process to become the finished contact products, resulting in low material utilization and high preparation costs.

[0004] In order to solve the above problems, the present invention decides to design a preparation method of a large-scale powder metallurgy copper-chromium contact material. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a large-scale powder metallurgy copper-chromium contact material.

[0006] A method for preparing a large-scale powder metallurgy copper-chromium contact material comprises the following steps: S1. Mixing: Mix 25-55% by mass of chromium powder and the remainder of copper powder for 2-7 hours to obtain a mixture; S2, Cold Isostatic Pressing: The mixed material obtained in step S1 is put into a rubber sleeve for grinding, and then cold isostatic pressing is performed at a pressure of 150-300 MPa and a holding time of 7-10 min to obtain a green body with a density of 78-82%; S3, vacuum sintering: The green body obtained in step S2 is placed in a vacuum sintering furnace for gradient sintering with a vacuum degree of 1×10 -4 ~1×10 -1 Pa, get the bar stock; S4. Vacuum degassing: The rod obtained in step S3 is encapsulated, and then placed in a heat treatment furnace and heated to 500-600°C, and then degassed for 8-20 hours until the vacuum degree in the encapsulation reaches 1×10 -5 ~1×10 -3 After Pa, the sheath is sealed by argon arc welding to obtain the sealed bar material; S5, Hot Isostatic Pressing: The sealed and welded rod material is hot isostatically pressed together with the sheath, and the sheath is removed after the hot isostatic pressing is completed to obtain the copper-chromium contact material.

[0007] Furthermore, in step S1, the particle size of the chromium powder and the copper powder is -200 mesh.

[0008] Description: -200 mesh powder can make the top of the contact have good density and chemical stability, providing additional conductivity and corrosion resistance.

[0009] Furthermore, in step S1, the mixing method is: mixing with a double-roll screw mixer, and the rotation speed of the double-roll screw mixer is 10~60r / min.

[0010] Description: The double helix structure enables the material to be fully stirred, convected, sheared and diffused during the mixing process, thereby achieving a fast and uniform mixing effect and ensuring the stability of product quality.

[0011] Furthermore, in step S2, the method of milling is: mechanically vibrating the rubber sleeve for 30 to 50 seconds, milling it 8 to 10 times, then covering it with the rubber sleeve and rolling it for 3 to 8 minutes, tightening the mouth of the rubber sleeve with a steel clip, with the rubber sleeve facing downward, and then milling it in the reverse direction for 2 to 3 times.

[0012] Note: The above-mentioned method of rolling the flour can make the flour raw materials loosen more fully in the initial stage, vibration can break up the possible lumps of flour, and reverse rolling can eliminate the internal stress that may be generated in the previous rolling process to a certain extent.

[0013] Furthermore, in step S2, the material of the rubber sleeve is selected from polyurethane or nitrile rubber.

[0014] Description: Polyurethane material has excellent wear resistance. When rolling and kneading, the rubber sleeve may move repeatedly on the rough surface. Polyurethane material can withstand this friction and reduce wear; nitrile rubber has good sealing performance. When the rubber sleeve mouth is tightened with a steel clip, the nitrile rubber can fit tightly, effectively preventing air from entering the rubber sleeve and keeping the internal environment relatively stable.

[0015] Further, in step S3, the gradient sintering method is: first, heat from room temperature to 290-310°C for 1.8-2.2h, and keep warm for 1.8-2.2h; then heat to 490-510°C for 2.8-3.2h, and keep warm for 1.8-2.2h; then heat to 890-910°C for 1.8-2.2h, and keep warm for 0.8-1.2h; finally, heat to 1020-1060°C for 2.8-3.2h, and keep warm for 2-3h, and stop heating and cool to 60°C with the furnace before taking out of the furnace.

[0016] Note: During the vacuum sintering process, thermal stress will be generated inside the material due to temperature changes. If the copper-chromium bar is heated to the highest temperature at one time, the inner and outer layers of the bar will generate large thermal stress due to the large temperature difference. The use of gradient heating can gradually increase the temperature of the bar, reduce the temperature difference between the inner and outer layers, and effectively reduce thermal stress.

[0017] Furthermore, in step S4, the material of the sheath is selected from a steel sheath or a copper sheath.

[0018] Note: Steel sleeves and copper sleeves can reduce the erosion of the gas on the sleeve during degassing, and good thermal conductivity also helps the bar to be heated evenly.

[0019] Furthermore, the diameter of the copper-chromium contact material obtained in step S5 is 70-100 mm.

[0020] Note: During the sintering process, large-sized contacts are more prone to component segregation. During the sintering process, as the size of the contacts increases, the elimination of internal pores becomes more complicated. Therefore, this application can reduce the difficulties in the preparation process of large-sized contact materials and maintain the good performance of large-sized contact materials.

[0021] As a solution of the present invention, in step S5, the temperature of hot isostatic pressing sintering is 800-960° C., the pressure is 110-130 MPa, and the holding time is 3-5 hours.

[0022] Note: The above hot isostatic pressing sintering parameters allow the gas inside the material to be discharged more fully.

[0023] As another solution of the present invention, in step S5, hot isostatic pressing is performed by zone pressing, and the method is as follows: With the center of the end face of the bar as the center of the circle, draw n concentric circles on the end face to divide the end face of the bar into n+1 areas, where n is an integer between 4 and 7; The radius R1 of the first area located in the center is the end radius R of the bar n The radius R of the concentric circle corresponding to the i-th area from the inside to the outside i =(R n -R i-1) / a(n-1); where a is a constant, ranging from 0.6 to 0.7, 2≤i≤n, and the radius of the concentric circles corresponding to each area is in mm; Starting from the first area, hot isostatic pressing is performed on each area from the inside to the outside; Among them, the hot isostatic pressing temperature of the first zone is T1=850~950℃, and the hot isostatic pressing pressure is P1=120~130MPa; The hot isostatic pressure P of the i-th region i =0.05(R i -R i-1 ) i-1 , hot isostatic pressing temperature T i =T1-(i-1)×ΔT1, ΔT1=150~200℃; When T i When <100℃, the hot isostatic pressure P of the i-th region to the n+1-th region i =1~10MPa, hot isostatic pressing temperature T i =T i-1 -ΔT2, ΔT2=20~30℃; The hot isostatic pressing time in each area is 30~60min.

[0024] Description: Use regional hot isostatic pressing, and process gradually from the center of the end face of the bar to the outside. During the overall hot isostatic pressing process of the bar, since each part is subjected to pressure and temperature changes at the same time, the expansion and contraction degrees of different areas may be different, which is easy to cause stress concentration inside the material. Since the present application performs hot isostatic pressing on different circular areas in a certain radius sequence and pressure and temperature gradient, the internal structure of the material can be made more uniform; this gradually changing condition can make the deformation and densification process of the material in different areas more moderate, and reduce defects such as cracks caused by internal stress during subsequent use. Therefore, the uniform structure obtained by regional hot isostatic pressing can make the conductivity of the copper-chromium contact more stable and the contact resistance smaller. In terms of mechanical properties, reducing internal stress concentration can improve the strength and toughness of the material, so that it can withstand higher currents and mechanical shocks during actual use.

[0025] Compared with the existing method for preparing copper-chromium contact materials, the beneficial effects of the present invention are: (1) The preparation method of the present application can prepare contact materials with larger specifications, which reduces the investment in large-tonnage presses and molds compared to ordinary molding. Compared with direct sheathing cold isostatic pressing and then hot isostatic pressing, the rod sintering and straightening process is added, and the straightening process and material loss before the rod sheathing are reduced, which greatly improves the material utilization rate and reduces the cost. In addition, the gas content of the material is lower by first degassing by cold isostatic pressing, then degassing by vacuum sintering, and then degassing by hot isostatic pressing.

[0026] (2) The present application adopts gradient sintering during vacuum sintering, which can allow the particles enough time to diffuse and arrange initially at a lower temperature stage. As the temperature gradually increases, the particles are more tightly and evenly bonded. When gradient heating is adopted, at a lower temperature stage, the gas inside the material has a chance to escape slowly. As the temperature gradually increases, the diffusion rate of the gas will also increase, and the gas inside the material can be discharged more fully.

[0027] (3) This application adopts regional hot isostatic pressing, which is carried out step by step from the center of the end face of the bar to the outside. Since hot isostatic pressing is carried out on different concentric circular areas in a certain radius sequence and pressure and temperature gradient, the internal structure of the material can be made more uniform; this gradually changing condition can make the deformation and densification process of the material in different areas more moderate, and reduce defects such as cracks caused by internal stress during subsequent use. Therefore, the uniform structure obtained by regional hot isostatic pressing can make the conductivity of the copper-chromium contact more stable and the contact resistance smaller. In terms of mechanical properties, reducing internal stress concentration can improve the strength and toughness of the material, so that it can withstand higher currents and mechanical shocks during actual use. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 1 is a metallographic image of the copper-chromium contact material of Example 1 of the present invention at 100X. DETAILED DESCRIPTION

[0029] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0030] Example 1: A method for preparing a large-scale powder metallurgy copper-chromium contact material, comprising the following steps: S1. Mixing: 40% by mass of chromium powder and the rest of copper powder are mixed for 4 hours, wherein the powder particle size of the chromium powder and the copper powder is -200 mesh, and the mixing method is: mixing with a double-roll screw mixer, the rotation speed of the double-roll screw mixer is 50r / min, to obtain a mixture; S2, Cold Isostatic Pressing: The mixed material obtained in step S1 is put into a rubber sleeve for grinding, and the material of the rubber sleeve is selected from polyurethane. The grinding method is: mechanically vibrate the rubber sleeve for 40 seconds, grind it 9 times, then cover the rubber sleeve with a rubber sleeve plug and roll the material for 6 minutes, tighten the rubber sleeve mouth with a steel clamp, with the rubber sleeve head facing down, grind it in the reverse direction for 2 times, and then perform cold isostatic pressing at a pressure of 225MPa and a holding time of 8 minutes to obtain a green body with a density of 80%; S3, vacuum sintering: The green body obtained in step S2 is placed in a vacuum sintering furnace for gradient sintering. The gradient sintering method is as follows: firstly, the temperature is raised from room temperature to 300°C for 2h, and kept at this temperature for 2h; then the temperature is raised to 500°C for 3h, and kept at this temperature for 2h; then the temperature is raised to 900°C for 2h, and kept at this temperature for 1h; finally, the temperature is raised to 1040°C for 3h, and kept at this temperature for 2.5h, and the heating is stopped and the green body is cooled to 60°C and taken out of the furnace. The vacuum degree is 1×10 -2 Pa, get the bar stock; S4. Vacuum degassing: The bar obtained in step S3 is sheathed, the sheath material is selected from steel sheath, and then placed in a heat treatment furnace and heated to 550°C, and then degassed for 14 hours until the vacuum degree in the sheath reaches 1×10 -4 After Pa, the sheath is sealed by argon arc welding to obtain the sealed bar material; S5, Hot Isostatic Pressing: The sealed rod material and the sheath are hot isostatically pressed together at a temperature of 880°C, a pressure of 120 MPa, and a holding time of 4 hours. After the hot isostatic pressing is completed, the sheath is removed to obtain a copper-chromium contact material with a diameter of 85 mm.

[0031] Example 2: This example is different from Example 1 in that 25% by mass of chromium powder and the remainder of copper powder are mixed for 2 hours, and the rotation speed of the double-roll screw mixer is 10 r / min.

[0032] Example 3: This example is different from Example 1 in that 55% by mass of chromium powder and the remainder of copper powder are mixed for 7 hours, and the rotation speed of the double-roll screw mixer is 60 r / min.

[0033] Example 4: This example is different from Example 1 in that the rubber sleeve is mechanically vibrated for 30 seconds, then powdered 8 times, and then covered with the rubber sleeve to plug the material for 3 minutes, the mouth of the rubber sleeve is tightened with a steel clip, the rubber sleeve head is facing downward, and then powdered in the reverse direction for 2 times.

[0034] Example 5: This example is different from Example 1 in that the rubber sleeve is mechanically vibrated for 50 seconds, then powdered 10 times, and then covered with the rubber sleeve and rolled for 8 minutes. The mouth of the rubber sleeve is tightened with a steel clip, with the rubber sleeve facing downward, and then powdered in the reverse direction for 3 times.

[0035] Example 6: This example is different from Example 1 in that the cold isostatic pressing pressure is 150 MPa and the holding time is 7 min.

[0036] Example 7: This example is different from Example 1 in that the cold isostatic pressing pressure is 300 MPa and the holding time is 10 min.

[0037] Example 8: The difference between this example and Example 1 is that the gradient sintering method is as follows: first, the temperature is raised from room temperature to 290°C for 1.8h, and then kept warm for 1.8h; then the temperature is raised to 490°C for 2.8h, and then kept warm for 1.8h; then the temperature is raised to 890°C for 1.8h, and then kept warm for 0.8h; finally, the temperature is raised to 1020°C for 2.8h, and then kept warm for 2h, and the heating is stopped and the furnace is cooled to 60°C and taken out of the furnace, and the vacuum degree is 1×10 -1 Pa.

[0038] Example 9: The difference between this example and Example 1 is that the gradient sintering method is as follows: first, the temperature is raised from room temperature to 310°C for 2.2h, and then kept warm for 2.2h; then the temperature is raised to 510°C for 3.2h, and then kept warm for 2.2h; then the temperature is raised to 910°C for 2.2h, and then kept warm for 1.2h; finally, the temperature is raised to 1060°C for 3.2h, and then kept warm for 3h. The heating is stopped and the furnace is cooled to 60°C and then taken out of the furnace. The vacuum degree is 1×10 -4 Pa.

[0039] Example 10: This example is different from Example 1 in that the package is placed in a heat treatment furnace and heated to 500°C, and then degassed for 8 hours until the vacuum degree in the package reaches 1×10 -3 Pa.

[0040] Example 11: This example is different from Example 1 in that the package is placed in a heat treatment furnace and heated to 600°C, and then degassed for 20 hours until the vacuum degree in the package reaches 1×10 -5 Pa.

[0041] Example 12: This example is different from Example 1 in that the hot isostatic pressing sintering temperature is 800°C, the pressure is 110 MPa, and the holding time is 3 hours.

[0042] Example 13: This example is different from Example 1 in that the hot isostatic pressing sintering temperature is 960°C, the pressure is 130 MPa, and the holding time is 5 hours.

[0043] Embodiment 14: This embodiment is different from Embodiment 1 in that the diameter of the copper-chromium contact material obtained in step S5 is 70 mm.

[0044] Embodiment 15: This embodiment differs from Embodiment 1 in that the diameter of the copper-chromium contact material obtained in step S5 is 100 mm.

[0045] Embodiment 16: This embodiment differs from Embodiment 1 in that, in step S5, hot isostatic pressing is performed by zone pressing, and the method is as follows: With the center of the end face of the bar as the center of the circle, draw n concentric circles on the end face to divide the end face of the bar into n+1 areas, where n is 5; The radius R1 of the first area located in the center is the end radius R of the bar n 20% of the total area, the radius R of the concentric circle corresponding to the i-th area from the inside to the outside i =(R n -R i-1 ) / a(n-1); where a is a constant, which is 0.65, 2≤i≤n, and the radius of the concentric circles corresponding to each area is in mm; Starting from the first area, hot isostatic pressing is performed on each area from the inside to the outside; Among them, the hot isostatic pressing temperature of the first zone is T1 = 900 °C, and the hot isostatic pressing pressure is P1 = 125 MPa; The hot isostatic pressure P of the i-th region i =0.05(R i -R i-1 ) i-1 , hot isostatic pressing temperature T i =T1-(i-1)×ΔT1, ΔT1=180℃; When T i When <100℃, the hot isostatic pressure P of the i-th region to the n+1-th region i =5MPa, hot isostatic pressing temperature T i =T i-1 -ΔT2, ΔT2=25℃; The hot isostatic pressing time of each area is 45 minutes.

[0046] Embodiment 17: This embodiment differs from Embodiment 16 in that the radius R1 of the first area located at the center is the radius R of the end face of the bar. n 15% of the total radius of the concentric circle corresponding to the i-th region from the inside to the outside is R i =(R n -R i-1 ) / a(n-1); where a is a constant, which is 0.7, and n is 4.

[0047] Embodiment 18: This embodiment differs from Embodiment 16 in that the radius R1 of the first area located at the center is the radius R of the end face of the bar. n 25% of the total area, the radius R of the concentric circle corresponding to the i-th area from the inside to the outside i =(R n -R i-1) / a(n-1); where a is a constant, which is 0.6, and n is 7.

[0048] Example 19: This example is different from Example 16 in that the hot isostatic pressing temperature T1 of the first zone is 850° C., and the hot isostatic pressing pressure P1 is 120 MPa; The hot isostatic pressure P of the i-th region i =0.05(R i -R i-1 ) i-1 , hot isostatic pressing temperature T i =T1-(i-1)×ΔT1, ΔT1=200℃; When T i When <100℃, the hot isostatic pressure P of the i-th region to the n+1-th region i =1MPa, hot isostatic pressing temperature T i =T i-1 -ΔT2, ΔT2=20℃; The hot isostatic pressing time of each area is 30 minutes.

[0049] Example 20: This example is different from Example 16 in that the hot isostatic pressing temperature T1 of the first zone is 950° C., and the hot isostatic pressing pressure P1 is 130 MPa; The hot isostatic pressure P of the i-th region i =0.05(R i -R i-1 ) i-1 , hot isostatic pressing temperature T i =T1-(i-1)×ΔT1, ΔT1=150℃; When T i When <100℃, the hot isostatic pressure P of the i-th region to the n+1-th region i =10MPa, hot isostatic pressing temperature T i =T i-1 -ΔT2, ΔT2=30℃; The hot isostatic pressing time of each area is 60 minutes.

[0050] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0051] The performance of the contact material prepared in each embodiment was tested.

[0052] 1. Investigate the effect of chromium powder ratio on the performance of contact materials. The results are shown in Table 1: Table 1 Performance data of contact materials of Examples 1 to 3

[0053] Combined with the results in Table 1 Figure 1 It can be seen that too small or too large a proportion of chromium powder will reduce the performance of the contact material. In comprehensive comparison, the parameter effect of Example 1 is relatively better.

[0054] 2. Investigate the influence of various parameters of the preparation steps and the specifications of the contact materials on the oxygen content and conductivity of the contact materials.

[0055] Table 2 Oxygen content and electrical conductivity of contact materials of Examples 4 to 15

[0056] It can be seen from the results in Table 2 that powder parameters that are too small or too large, cold isostatic pressing parameters that are too small or too large, gradient sintering parameters that are too small, heat treatment parameters that are too small, hot isostatic pressing parameters that are too small or too large, and excessive diameter of the copper-chromium contact material will all reduce the performance of the contact material. Among them, Example 8 has larger gradient sintering parameters and lower oxygen content than Example 1, Example 11 has a higher heating temperature and lower oxygen content than Example 1, and Example 14 has a smaller contact specification and the same conductivity as Example 1, but Example 8 and Example 11 have lower conductivity than Example 1, and Example 14 has a slightly higher oxygen content than Example 1. Therefore, from an economic point of view, the parameter effect of Example 1 is relatively better.

[0057] 3. Investigate the effect of hot isostatic pressing in different areas on the oxygen content and conductivity of the contact material.

[0058] Table 3 Oxygen content and electrical conductivity of contact materials of Examples 16 to 20 and Comparative Examples 1 to 3

[0059] The difference between Comparative Example 1 and Example 16 is that when T i When the temperature drops below 100°C, hot isostatic pressing is still carried out in the same manner as above 100°C; The difference between Comparative Example 2 and Example 16 is that the pressure difference in each concentric circle area is the same; The difference between the comparative example 3 and the example 16 is that the pressure values ​​of the concentric circle areas are the same; From the results in Table 3, it can be seen that the parameters of Examples 16 to 20 are more stable than those of Example 1, and the oxygen content is reduced and the conductivity is improved. Therefore, hot isostatic pressing in different regions has a certain effect on the performance of the copper-chromium contact material; and by comparing Example 16 with Control Example 3, it can be seen that the physical and chemical properties inside the copper-chromium contact material are not evenly distributed in different positions. In the center and edge of the bar, due to differences in factors such as heat conduction and component distribution, its response to hot isostatic pressing is also different. Control Example 1 lacks pressure adjustment for temperature changes below 100°C, and Control Examples 2 and 3 lack the pressure application rules for each concentric circle area. Compared with Examples 16 to 20, the reduction in oxygen content is weakened and the increase in conductivity is also weakened accordingly; By comparing Examples 16 to 20, it can be seen that if the intervals between the circular areas are too small or too large, and the pressure and temperature changes are too small or too large, the oxygen content reduction and conductivity increase of the copper-chromium contact material will be weakened. Therefore, in comprehensive comparison, the parameter effect of Example 16 is relatively better.

Claims

1. A method for preparing a large-scale powder metallurgy copper-chromium contact material, characterized in that: The following steps are involved: S1. Mixing: Mix 25-55% by mass of chromium powder and the remainder of copper powder for 2-7 hours to obtain a mixture; S2, Cold Isostatic Pressing: The mixed material obtained in step S1 is put into a rubber sleeve for grinding, and then cold isostatic pressing is performed at a pressure of 150-300 MPa and a holding time of 7-10 min to obtain a green body with a density of 78-82%; S3, vacuum sintering: The green body obtained in step S2 is placed in a vacuum sintering furnace for gradient sintering with a vacuum degree of 1×10 -4 ~1×10 -1 Pa, get the bar stock; S4. Vacuum degassing: The rod obtained in step S3 is encapsulated, and then placed in a heat treatment furnace and heated to 500-600°C, and then degassed for 8-20 hours until the vacuum degree in the encapsulation reaches 1×10 -5 ~1×10 -3 After Pa, the sheath is sealed by argon arc welding to obtain the sealed bar material; S5, Hot Isostatic Pressing: The sealed and welded rod material is hot isostatically pressed together with the sheath, and the sheath is removed after the hot isostatic pressing is completed to obtain the copper-chromium contact material.

2. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S1, the particle size of the chromium powder and the copper powder is -200 mesh.

3. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S1, the mixing method is: mixing with a double-roll screw mixer, and the rotation speed of the double-roll screw mixer is 10~60r / min.

4. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S2, the method of milling is: mechanically vibrating the rubber sleeve for 30-50 seconds, milling 8-10 times, then covering the rubber sleeve with the rolling material for 3-8 minutes, tightening the rubber sleeve mouth with a steel clip, with the rubber sleeve head facing down, and then milling in the reverse direction for 2-3 times.

5. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S2, the material of the rubber sleeve is selected from polyurethane or nitrile rubber.

6. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S3, the gradient sintering method is: first, heat from room temperature to 290-310°C for 1.8-2.2h, and keep warm for 1.8-2.2h; then heat to 490-510°C for 2.8-3.2h, and keep warm for 1.8-2.2h; then heat to 890-910°C for 1.8-2.2h, and keep warm for 0.8-1.2h; finally, heat to 1020-1060°C for 2.8-3.2h, and keep warm for 2-3h, and stop heating and cool to 60°C with the furnace before taking out of the furnace.

7. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S4, the material of the sheath is selected from a steel sheath or a copper sheath.

8. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: The diameter of the copper-chromium contact material obtained in step S5 is 70-100 mm.

9. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S5, the hot isostatic pressing sintering temperature is 800-960° C., the pressure is 110-130 MPa, and the holding time is 3-5 hours.

10. The method for preparing a large-scale powder metallurgy copper-chromium contact material according to claim 1, characterized in that: In step S5, hot isostatic pressing is performed by zone pressing, and the method is as follows: With the center of the end face of the bar as the center of the circle, draw n concentric circles on the end face to divide the end face of the bar into n+1 areas, where n is an integer between 4 and 7; The radius R1 of the first area located in the center is the end radius R of the bar n The radius R of the concentric circle corresponding to the i-th area from the inside to the outside i =(R n -R i-1 ) / a(n-1); where a is a constant, ranging from 0.6 to 0.7, 2≤i≤n, and the radius of each concentric circle area is in mm; Starting from the first area, hot isostatic pressing is performed on each area from the inside to the outside; Among them, the hot isostatic pressing temperature of the first zone is T1=850~950℃, and the hot isostatic pressing pressure is P1=120~130MPa; The hot isostatic pressure P of the i-th region i =0.05(R i -R i-1 ) i-1 , hot isostatic pressing temperature T i =T1-(i-1)×ΔT1, ΔT1=150~200℃; When T i When the temperature is less than 100℃, the hot isostatic pressure P of the i-th region to the n+1-th region i =1~10MPa, hot isostatic pressing temperature T i =T i-1 -ΔT2, ΔT2=20~30℃; The hot isostatic pressing time in each area is 30~60min.

Citation Information

Patent Citations

  • High-performance copper chromium contactor material and preparing method thereof

    CN105018768A

  • Production method for fine-grained low-oxygen CuCr contact material

    CN105734328A

  • High-quality copper-chromium alloy densifying technology

    CN106756174A

  • Preparation method of near-net-shape copper chromium contact material

    CN106756204A

  • Preparation method of high-performance powder metallurgy copper-chromium contact material

    CN118497534A

Cited By

  • Powder, metal part, electrical contact, method of manufacturing powder, and method of manufacturing metal part

    US20250170642A1